Perbedaan Kecemasan pada Ibu Hamil Resiko Tinggi dan Resiko Rendah di Puskesmas Brondong - Rizqullah, Rahadian; Eko Martini, Diah; Ekawati, Heny (Jurnal Keperawatan Muhammadiyah, 2026)
Anxiety is a common psychological issue experienced by pregnant women and can negatively impact both maternal and fetal health. High-risk pregnancy refers to a condition with a greater potential for complications compared to normal pregnancy, whereas low-risk pregnancy typically proceeds without significant risk factors or serious complications. This study aimed to examine differences in anxiety levels between high-risk and low-risk pregnant women at Brondong Public Health Center. A comparative study with a cross-sectional approach was conducted, involving 70 respondents selected through quota sampling. The research instruments included the Poedji Rochjati Risk Assessment Card to categorize pregnancy risk and the Depression Anxiety Stress Scale (DASS) to measure anxiety levels. The Mann-Whitney test revealed a p-value of 0.000 (p < 0.05), indicating a significant difference in anxiety levels, with high-risk pregnant women exhibiting higher anxiety compared to those with low-risk pregnancies. In conclusion, there is a significant difference in anxiety levels between high-risk and low-risk pregnant women at Brondong Public Health Center. These findings are expected to inform healthcare professionals in enhancing the quality and quantity of Antenatal Care (ANC) services by integrating targeted educational programs, particularly for high-risk pregnant women.